Depot-Based Delivery Systems for Pro-Angiogenic Peptides: A Review - Van Hove, Amy H.; Benoit, Danielle S. W. (Frontiers in Bioengineering and Biotechnology, 2015)
Insufficient vascularization currently limits the size and complexity for all tissue engineering approaches. Additionally, increasing or re-initiating blood flow is the first step towards restoration of ischemic tissue homeostasis. However, no FDA approved pro-angiogenic treatments exist, despite the many pre-clinical approaches that have been developed. The relatively small size of peptides gives advantages over protein-based treatments, specifically with respect to synthesis and stability. While many pro-angiogenic peptides have been identified and shown promising results in vitro and in vivo, the majority of biomaterials developed for pro-angiogenic drug delivery focus on protein delivery. This narrow focus limits pro-angiogenic therapeutics as peptides, similar to proteins, suffer from poor pharmacokinetics in vivo, necessitating the development of controlled release systems. This review discusses pro-angiogenic peptides and the biomaterials delivery systems that have been developed, or that could easily be adapted for peptide delivery, with a particular focus on depot-based delivery systems.